Analisis Sistem Pendukung Keputusan Pemilihan Peralatan Teknis Menggunakan Metode Analytical Hierarchy Proccess - Tata Sutabri; Annisa Fitri Aulia (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
Selection of the best technical equipment in a company is a step that can be taken to determine the selection of goods that are most appropriate and suit your needs. The problems that occur in the process of selecting technical equipment in companies are still not accurate because there is no information system available to support this process. By referring to the needs that occur, decision support applications are needed to be a solution to the problems that occur, especially in the process of automating value input and the ranking calculation process. This research aims to make a proposal for creating a decision support system to solve the above problems using the Analytical Hierarchy Process (AHP) method. This method is applied to the decision making process based on criteria set by the company including suitability of specifications, stock availability and speed of delivery. From the results of calculations that have been carried out using the AHP method to obtain technical equipment results that best meet the criteria of the 5 technical equipment provider partners included in the assessment criteria. The results of calculations using the AHP method show accuracy in obtaining recommendations for the sequence of technical equipment.